Investigating Balance Perception and Balance Performance in Neurological Disorders for Targeted Rehabilitation Strategies. - Cardini, Rebecca; Torchio, Alessandro; Aprile, Irene; Turolla, Andrea; Cattaneo, Davide; Gervasoni, Elisa (PTJ: Physical Therapy & Rehabilitation Journal, 2025)
Importance Task-specific balance deficits are common in people with neurological disorders (PwND), significantly affecting their activities of daily living (ADLs). However, the relationship between balance deficits and ADLs measured by patient-reported outcomes is poorly understood, thus limiting the selection of specific static and dynamic tasks to be used to train for a given activity. Objective The aim of the study was to provide a clinical framework linking ADLs, balance tasks, and balance resources to support clinicians' decision-making when planning task-oriented balance rehabilitation for PwND. Design This was an observational study with a cross-sectional design. Setting This study examined clinical contexts involving PwND. Participants This study involved people with Parkinson disease, stroke, or multiple sclerosis (MS). Exposure The study used the Activities-Specific Balance Confidence (ABC) Scale for patient-reported outcomes to assess perceived balance during ADLs, and the Berg Balance Scale (BBS) and Dynamic Gait Index (DGI) to evaluate static and dynamic balance. Main Outcomes and Measures Kendall tau correlations (τ) were used to identify meaningful associations between ABC and BBS–DGI items, matching ADLs with specific balance tasks. Results The study sample comprised 299 people with Parkinson disease (n  = 94), stroke (n  = 94), and MS (n  = 111) with a median (interquartile range) age of 63 (52.0-71.5) years, all exhibiting moderate to severe balance impairments. Moderate correlations (τ  ≥ 0.39) were found between dynamic and semi-dynamic challenging outdoor ADLs with static and dynamic tasks involving sensory orientation and the use of vestibular and proprioceptive systems. Moreover, stability limits-verticality, anticipatory postural adjustments, and stability in gait are the primary balance resources to consider when designing ad hoc rehabilitation interventions. Conclusions This study establishes associations between specific ADLs and balance tasks, offering a clinical framework to identify relevant balance resources for rehabilitation. It provides clinicians with a structured approach for planning task-oriented, needs-based balance rehabilitation for PwND, focusing on the training of specific balance resources to enhance ADLs. Relevance This study provides a clinical framework to help clinicians in planning task-oriented and needs-based balance rehabilitation for PwND, suggesting which balance resources should be trained to improve specific ADLs.